The wisdom and humor of Hodja Nasreddin in the context of various versions of the parable of kazan - Kenzhekozhayeva, Akbota; Mambetov, Zholdasbek O.; Auyesbaeva, Pakizat T. (The New Research of Tuva, 2025)
The article examines three national versions (Kazakh, Uighur, and Uzbek) of the parable about the cauldron, in which the qualities of Hodja Nasreddin are reflected, and the process of adaptation and transformation of the text is shown depending on the cultural and literary contexts of Turkic peoples. The source base includes the following texts: the Kazakh parable “The Deceased Cauldron”, the Uighur version “The Cauldron Was Pregnant”, and the Uzbek version “Can a Cauldron Die?”. The study identifies and describes similarities among the versions, as well as differences in plotlines, character descriptions, and actions. It is noted that Hodja Nasreddin does not engage in open confrontation, but rather takes advantage of the situation, employing humor; his actions are grounded in folk wisdom. The article discusses various interpretations of his image and its manifestations within national traditions. Special attention is given to the adaptability of Hodja Nasreddin’s character to changing conditions.